Educação e Política em Angola. Uma proposta de diferenciação social - Maria João da Silva Mendes Ferreira (Cadernos de Estudos Africanos)
Through this text we would like to show that education is a strong and reliable item when political changes are being evaluated. However the goals of this investigation in which this text is included are larger. We would also like to show how important education is to the development of societies and to classify schools in Angola. During the political transition from a socialist system towards a capitalist one, the strategies designed to have access to education allow us to distinguish different social classes as well as different educational contexts. Society recognises that getting education is the main vehicle for social mobility, that's why families develop strategies which enables them to solve their educational problems.